Expanding the neutralization scope of the EchiTAb-plus-ICP antivenom to include venoms of elapids from Southern Africa. (January 2017) - Sánchez, Andrés; Segura, Álvaro; Vargas, Mariángela; Herrera, María; Villalta, Mauren; Estrada, Ricardo; Wu, Francisco; Litschka-Koen, Thea; Perry, Michael Alfred; Alape-Girón, Alberto; León, Guillermo
Abstract: EchiTAb-plus-ICP is an antivenom prepared from plasma of horses hyperimmunized with the venoms of the carpet viper ( Echis ocellatus ), the puff adder ( Bitis arietans ) and the black-necked spitting cobra ( Naja nigricollis ). Therefore, the use of this antivenom has been limited to Western Africa. In order to expand the neutralization scope of EchiTAb-plus-ICP, we supplemented the immunogenic mixture with the venoms of B. arietans, the black mamba ( Dendroaspis polylepis ), the Mozambique spitting cobra ( Naja mossambica ), the snouted cobra ( N. annulifera ), and the rinkhals ( Hemachatus haemachatus ) from Swaziland. The ability of the expanded-scope antivenom, hereby named EchiTAb + ICP, to neutralize the venoms of B. arietans, D. polylepis, N. mossambica and H. haemachatus was similar to those of FAV Afrique and the SVA African antivenoms. In comparison to the SAIMR antivenom, the expanded-scope EchiTAb + ICP had lower ability to neutralize the venom of B. arietans, but similar ability to neutralize the venoms of D. polylepis, N. mossambica and H. haemachatus . Owing to its low protein concentration, the expanded-scope EchiTAb + ICP had lower ability to neutralize the venom of N. annulifera than FAV Afrique and the SAIMR antivenoms. However, when formulated at a protein concentration as high as FAV Afrique and SAIMR antivenoms, the expanded-scope EchiTAb + ICP showed similar capacity to neutralize this poorly immunogenic venom. Our results encourage the transition to the new EchiTAb + ICP antivenom, with an expanded neutralization scope that includes venoms of some of the most medically important elapids from Southern Africa. Clinical trials are required to determine the minimum effective-safe dose of the new EchiTAb + ICP for each type of envenomation. Highlights: EchiTab-plus-ICP is an antivenom towards venoms of snakes from Western Africa. Venoms of elapids from Swaziland were included in the immunization mixture. The neutralization scope of the EchiTab-plus-ICP was expanded to include venoms of elapids from Southern Africa. The expanded-scope antivenom has neutralization properties similar to FAV Afrique and the SVA African antivenoms. The clinical efficacy of the new EchiTab-plus-ICP in envenomations caused by elapids from Southern Africa is pending.